Complete Consistency of the Estimator of Nonparametric Regression Models Based on ρ~-Mixing Sequences - Xuejun Wang; Fengxi Xia; Meimei Ge; Shuhe Hu; Wenzhi Yang (Abstract and Applied Analysis)
We study the complete consistency for estimator of nonparametric regression model based on ρ~-mixing sequences by using the classical Rosenthal-type inequality and the truncated method. As an application, the complete consistency for the nearest neighbor estimator is obtained.